Micro Propagation of Several Potted Anthurium Accessions Using Spathe Explants - Budiarto, Kurniawan (Jurnal Natur Indonesia, 2008)
The introduction of new varieties and production system of anthuriums has faced some problems due to the lowmultiplication rates in conventional vegetative and genotypic alteration problem in reproductive propagation. Sincethen, in vitro propagation technique became important to be investigated. The research was carried out fromSeptember 2006 to August 2007 at the Indonesian Ornamental Crops Research Institute. A complete factorialexperiment was designed to accomplish two chronological in vitro activities. The first step dealt with differentincubation sites, i.e. dark and light conditions for callus induction of three potted anthurium accessions, namelyclone no. SM. 001, cv. Alphine and cv. Bonito. The best callus obtained from the incubation treatment were then,transferred into defined media with different formulations to get free-callus plantlets in the second steps. Theresults showed that more progressive callus development from spathe explant was detected on the media ofmodified Nitsch and Nitsch + 1 mg/l 2,D + 1 mg/l Kin + 1 mg/l BA stored at dark after 60 days incubation. After 45days transferring the callus in the same media on light conditions, torpedo-shaped callus was detected. Completeplanlets were obtained after 75 days reculturing the buds in Nitsch and Nitsch medium containing 2,4 D withvarious BA concentrations. Clone SM. 001 and cv. Bonito showed higher number of visible shoot and rootdevelopments compared to cv. Alphine. In general, better shoot and root developments and higher planlets survivedafter acclimatization were observed on the BA concentrations of 2 and 3 mg/l.